ANALISIS PENYUSUNAN ANGGARAN DAN REALISASI BELANJA DAERAH PADA BADAN PERENCANAAN PENELITIAN DAN PENGEMBANGAN DAERAH KOTA MANADO - Mentang, Fanda; Sabijono, Harijanto; Pangerapan, Sonny (Universitas Sam Ratulangi, 2020)
Expenditure is one component that is of public concern in the Budget Realization Report. This study aims to: (1) find out the procedures for preparing the budget for the Manado City Regional Research and Development Planning Board (2) find out the consideration factors in preparing the budget for the Manado City Regional Research and Development Planning Board (3) Analyze the difference between the realization with a budget for the Manado City Regional Research and Development Planning Agency. The analytical method used in this thesis research is a descriptive method in which all data relating to the budget are collected to be analyzed and then drawn a conclusion. The results obtained show that the procedures for preparing the budget and the factors considered in preparing the budget are good, even in the implementation of the preparation are in accordance with the guidelines and the results of the analysis of variance (deviations) from the 2016-2018 fiscal year are still profitable because the realization is still lower than budgeted.